Analysis of the Effect of the People's Business Credit (KUR) Program on the Income of Rice Paddy Farmers in South Konawe Regency - Alfitrah La Hini; Azhar Bafadal; Yusna Indarsyih (International Journal of Technology and Education Research, 2025)
This research was motivated by challenges in the development of agricultural businesses due to limited capital and difficulties in accessing funding sources. To strengthen the capital capacity of agricultural businesses, the government launched the People's Business Credit (KUR) program with low-interest rates aimed at farmers. This study aims to: (1) determine the income level of rice paddy farmers in Konawe Selatan Regency, and (2) analyze the impact of the KUR program on the income of rice paddy farmers in Konawe Selatan Regency. The population of this study consisted of all rice paddy farmers in Ranomeeto and Ranomeeto Barat Districts who utilized KUR loans. The sampling technique used was non-probability sampling with a purposive sampling approach, involving 60 farmers who met the criteria. The data analysis was conducted using income analysis and double-logarithm regression analysis with F-test and t-test. The results showed that the average income of rice paddy farming was IDR 16,697,234 per harvest. The variables of KUR interest rates and the amount of KUR loans were positively correlated but did not have a significant impact on the income of rice paddy farmers